2006
DOI: 10.4049/jimmunol.177.2.1085
|View full text |Cite
|
Sign up to set email alerts
|

Grb2 and Gads Exhibit Different Interactions with CD28 and Play Distinct Roles in CD28-Mediated Costimulation

Abstract: Although both CD28 and ICOS bind PI3K and provide stimulatory signal for T cell activation, unlike CD28, ICOS does not costimulate IL-2 secretion. CD28 binds both PI3K and Grb2, whereas ICOS binds only PI3K. We have generated an ICOS mutant, which can bind Grb2 by replacement of its PI3K binding motif YMFM with the CD28 YMNM motif, and shown that it induces significant activation of the IL-2 promoter. However, this mutant ICOS was insufficient to activate the NF-κB pathway. In this study, we show that Gads, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
4
48
1
Order By: Relevance
“…CD28 has several Src homology (SH)-2 binding domains (e.g., YMNM) which are able to bind p85, the regulatory subunit of PI3K, and is a potent activator of PI3K (19). CD28 has a cytoplasmic domain of approximately 40 amino acid residues that is highly conserved across species and that contains four tyrosine residues (Y170, 185, 188, 197), potentially mediating protein-protein interactions.…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…CD28 has several Src homology (SH)-2 binding domains (e.g., YMNM) which are able to bind p85, the regulatory subunit of PI3K, and is a potent activator of PI3K (19). CD28 has a cytoplasmic domain of approximately 40 amino acid residues that is highly conserved across species and that contains four tyrosine residues (Y170, 185, 188, 197), potentially mediating protein-protein interactions.…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…In the presence of costimulation, T cells would secrete large amounts of IL-2, IL-4, interferon (IFN)-γ, etc., and undergo differentiation into Th1/Th2/Th17 (34-37). CD28 engagement induces massive IL-2 secretion, which is dependent upon the activation of mitogen-activated protein (MAP) kinase (19,38). Using yeast-hybrid technique, a novel CD28 cytoplasmic tail (CD28 CYT) interacting protein, the MAP kinase phosphatase-6 (MKP6) was isolated, which showed to inactivate MAP kinases, so it is associated with cytokine secretion (39).…”
Section: Intracellular Signals Of Costimulation In T Cell Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is more likely that CD4 + cells are the main drivers of the EAE phenotype observed in Grb2 fl/fl CD4cre tg mice. Mechanistically, it was demonstrated that Grb2 is necessary for the induction of IL-2 secretion via CD28 (40), and it is also necessary to induce a mitogenic response via IL-2R (31,41). This might explain why proliferation of Grb2-deficient CD4 + T cells is diminished after stimulation with IL-2.…”
Section: Discussionmentioning
confidence: 97%
“…Y191 is contained in the YMNM motif involved in the recruitment of both Grb-2 [13] and the p85 subunit of the PI3K [14]. Y206 and Y209 are contained in the C-terminal prolinerich motif (YQPYAPP) that has been recently involved in the regulation of several CD28 functions [15][16][17][18]. The two tyrosine residues Y206/209, within the C-terminal proline-rich motif of CD28, have been described to exert a key role in CD28-regulated HIV-1 transcription, whereas disruption of the PI3K binding motif, by mutating Y191, increased HIV-1 transcription [1,19].…”
Section: Resultsmentioning
confidence: 99%